Overcoming seed dormancy and initial seedling growth of umbu tree in the submedium São Francisco - Brito, Antônio Marcos de Oliveira; Rocha, Aline; Silva, Rangel Ferreira da; Nascimento, Antônia Antunes do (Research, Society and Development, 2024)
The umbu tree is an endemic species of the Brazilian semi-arid region, capable of surviving and producing under conditions of low rainfall. Its seeds exhibit dormancy, which needs to be overcome to achieve rapid and uniform emergence. The aim was to analyze techniques for overcoming dormancy in umbu tree seeds that can increase the percentage and reduce the time of emergence, and to analyze the initial development of seedlings. The umbu fruits were harvested ripe in Casa Nova/BA, depulped, the seeds were dried in the shade, and stored in a cardboard box for approximately seven months. The treatments were: control, distal cut, distal cut plus immersion in water for 24h, distal cut plus immersion in GA3 1000µL.L-1 for 24h, immersion of seeds without cut in water for 24h, immersion of seeds without cut in Gibberellic Acid (GA3) 1000µL.L-1 for 24h, and seeds that passed through the digestive tract of ruminants. Seedlings began to emerge 11 days after planting seeds that were treated with distal cut and immersion in water for 24h, distal cut and immersion in GA3 for 24h, and those that passed through the digestive tract of ruminants. Control seeds and those immersed in water and GA3 for 24h showed the highest rates of emergence speed and emergence percentage, exceeding 90%. For seedling development index and average emergence time, there was no difference between treatments. Therefore, seeds stored for seven months can emerge without undergoing any treatment, and the distal cut anticipates emergence.